La Greta Thunberg du Le grand livre du climat - Ludovic Aubin; Renaud Hétier; Cécile Redondo; Nathanaël Wallenhorst (Éducation et Socialisation)
Our study focuses on Greta Thunberg and her Great Climate Book, with a view to identifying the key principles that inspire democratic socialisation in and through education. This contemporary activist is involved in media coverage of the climate and ecological cause, and embodies a message that concerns the transmission of biogeophysical scientific knowledge, and a political and media commitment to achieving socio-political breakthroughs that will guarantee the sustainability of human life in society in the Anthropocene epoch. We propose three focal points for the analysis of this work. 1. A scientific focus: his understanding of the functioning of the Earth system based on his reading of biogeophysical literature, which enables him to give precedence to the paradigm of rupture over that of continuity/growth. 2. A political focus: his political thinking is committed to democracy (both in the mobilisation of citizens and in the operation of institutions). 3. An educational focus: his attachment to scientific knowledge and its transmission, but also his awareness of the way in which education is a privileged means of sustainable change.